WAKOWAJI (Waras Ekonomi Waras Jiwa) Peningkatan Produktivitas Era New Normal di Desa Mulo, Wonosari, Gunungkidul - Nurlia Ikaningtyas; Ongki Ongki; Feliks Hendrikjayanto Laoli; Wayan Agus Wijane; Wisnu Wijaya Saputra; Galuh Novita Sari; Ella Sri Ardini; Diah Listiani; Oktavianna Kusuma Ningrum; Beatrich Alfika Manu Putri (Pelita Abdi Masyarakat, 2021)
Background : Gunungkidul Regency has a topography where the majority of its territory is in the form of karst hilly areas which make agricultural land less fertile. This has an impact on agricultural cultivation which from year to year has not shown optimal results and the low level of the community's economy and high poverty in the Gunungkidul region. The number of people with low incomes is one of the reasons for the high number of people with psychosocial disabilities in Gunungkidul. The number of ODDP in Mulo Village is 18 people. Based on the screening that has been carried out, the following results are obtained, namely one person is in the acute category, two people are in the maintenance category, and 15 people are in the health promotion category. This has had a negative impact on the economy of the people of Mulo Village. The purpose of this program is to develop the potential of natural resources, to explain the factors that influence the high cases of mental health problems, to find out how much influence the economy has on the mental health of the people of Mulo Village in the new normal era. Method : The method of implementing activities is carried out offline (outside the network), with activity stages starting from screening, categorizing, giving intervention in the form of Group Activity Therapy (GAT), Self Help Group (SHG) and people with psychosocial disabilities empowerment by making manggleng and raising goats. Result : The results of the six indicators that have been implemented are an increase in behavior change. People with psychosocial disabilities is able to carry out positive activities independently such as taking medication regularly, being able to express opinions, and work according to the skills and abilities possessed in the new normal era. Conclussion : People with psychosocial disabilities is able to interact socially with local residents and be able to increase economic productivity in the form of manggleng-making and goat farming.